Multistage Increase of Websites Effectiveness - Jankowski, Jarosław (Wieloetapowe zwiększanie efektywności witryn internetowych, 2011)
The evolution of Internet platforms influences the need to develop systems focused on the increase of their effectiveness. In case of complex systems the selection of functioning parameter is important, as well as conduction of test research in order to provide a determined level of effectiveness including maximization of results in many scopes. The article presents the multistage procedure which enables the reduction of decision problem dimension and increase of the effectiveness of Internet websites with the use of factor analysis method.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 187, s. 219-229
Keywords: biznes elektroniczny; platformy internetowe; wieloczynnikowa analiza porównawcza; witryny internetowee-business; internet platforms; multivariate comparative analysis; internet websites